2002
DOI: 10.1086/340236
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficileToxin A Alters In Vitro–Adherent Neutrophil Morphology and Function

Abstract: The effects of purified toxin A in vitro on the shape and function of polymorphonuclear leukocytes (PMNL) were examined. Toxin A induced changes in adherent PMNL shape from a compact spherical or pyramidal shape to a thin and rope-like shape. This change in shape was accompanied by rearrangement of the F-actin cytoskeleton into aggregates. Toxin A-treated PMNL exhibited increased adherence and expressed less L-selectin and more Mac-1, compared with untreated PMNL. In contrast to these proinflammatory actions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…We now show that in the presence of EHNA, the effects of ATL313 are much weaker than when the agonist is used alone, which indicates that most of the anti-inflammatory effects of EHNA observed in our model rely on its ability to enhance the concentration of adenosine in the ileal tissue that maximally stimulates A2A receptors. The abundant presence of neutrophils within TxA-induced pseudomembranes is well known (9,34), as is their important role in the pathogenesis of ileal damage induced by C. difficile TxA (2,27). Here, we showed that EHNA reduced TxA-induced MPO activity, suggesting a potent effect of EHNA to inhibit neutrophil infiltration into ileal tissue.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We now show that in the presence of EHNA, the effects of ATL313 are much weaker than when the agonist is used alone, which indicates that most of the anti-inflammatory effects of EHNA observed in our model rely on its ability to enhance the concentration of adenosine in the ileal tissue that maximally stimulates A2A receptors. The abundant presence of neutrophils within TxA-induced pseudomembranes is well known (9,34), as is their important role in the pathogenesis of ileal damage induced by C. difficile TxA (2,27). Here, we showed that EHNA reduced TxA-induced MPO activity, suggesting a potent effect of EHNA to inhibit neutrophil infiltration into ileal tissue.…”
Section: Discussionmentioning
confidence: 57%
“…The mechanism of TxA-induced enteritis involves toxin binding to enterocyte receptors, leading to the activation of sensory and enteric nerves that results in enhanced intestinal secretion and motility, the degranulation of mast cells, and the infiltration of the mucosa by neutrophils (9,27,39). In addition to its proinflammatory and prosecretory activities, TxA induces cell death in human and murine cells, which could contribute to intestinal mucosal disruption (7,10).…”
mentioning
confidence: 99%
“…Mucosal damage is sustained by an intense host inflammatory response, particularly in those with the 027 ribotype (28,29), and this condition frequently persists despite the administration of appropriate antibiotic therapy (30). Moreover, toxin production exerts mucosal immunity impairment by the modification of neutrophil morphology and function (31). Moreover, a significant number of patients of the CDI/BSI ϩ group received immunosuppressive therapies, especially steroids, and this factor can be involved in an increased susceptibility to invasive infections.…”
Section: Discussionmentioning
confidence: 99%
“…MPO activity within tissues has been used to indicate neutrophil infiltration (44). The important role of neutrophils in the pathogenesis of colitis caused by infection with C. difficile and the abundant presence of neutrophils within TxA-induced pseudomembranes are well known (6,27). Inhibition of neutrophil recruitment by antibodies to ␤ 2 -integrins or P-selectin decreases intestinal damage in TxA-exposed animals (19,21).…”
Section: Discussionmentioning
confidence: 99%